Neurological adverse event profile of magnetic resonance imaging–guided focused ultrasound thalamotomy for essential tremor. Issue 5 (27th April 2018) - Fishman, Paul S.; Elias, W. Jeffrey; Ghanouni, Pejman; Gwinn, Ryder; Lipsman, Nir; Schwartz, Michael; Chang, Jin W.; Taira, Takaomi; Krishna, Vibhor; Rezai, Ali; Yamada, Kazumichi; Igase, Keiji; et al.
ABSTRACT: Background: Magnetic resonance imaging–guided focused ultrasound thalamotomy is approved by the U.S. Food and Drug Administration for treatment of essential tremor. Although this incisionless technology creates an ablative lesion, it potentially avoids serious complications of open stereotactic surgery. Objective: To determine the safety profile of magnetic resonance imaging–guided focused ultrasound unilateral thalamotomy for essential tremor, including frequency, and severity of adverse events, including serious adverse events. Methods: Analysis of safety data for magnetic resonance imaging–guided focused ultrasound thalamotomy (186 patients, five studies). Results: Procedure‐related serious adverse events were very infrequent (1.6%), without intracerebral hemorrhages or infections. Adverse events were usually transient and were commonly rated as mild (79%) and rarely severe (1%). As previously reported, abnormalities in sensation and balance were the commonest thalamotomy‐related adverse events. Conclusion: The overall safety profile of magnetic resonance imaging–guided focused ultrasound thalamotomy supports its role as a new option for patients with medically refractory essential tremor. © 2018 International Parkinson and Movement Disorder Society